The Analysis of Comparative Advantage in some of Newly Industrialized Countries of South-East of Asia and Comparing it with Iran - Bagher Darvishi; Heshmatolah Asgari (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2006)
In recent years, the rapid economic growth of newly industrialized countries has amazed every body, since during a short period of time, they had experienced extensive economic growth rate. Different economist explained and justified this phenomenon in different ways, the importance of this issue can be considered as a main stimulation which motivated us to investigate the comparative advantage of various economic sections of these countries and compare them with Iran in order to answer the following questions. 1. Do newly industrialized countries have worked based on comparative advantage? 2. does the comparative advantage in industrial section can be considered as a cause which brings the rapid growth in such countries? 3. How is Iran's situation in this matter? In order to answer to above mentioned questions, we have tried to compare the comparative advantage index in main industrial, agricultural and service section's, in these countries during 1984-2000. We have used pooling data in estimating the rate of economic growth. So these countries on comparative advantage of various sections, as a result we can say that, industry and creation of comparative advantage in this section is the most influential factors which cause such an increasing growth in newly industrialized countries. In Iran, we can say that it has not changed its advantage in the same way, but it has focused on agricultural section, which on the basis of research finding, it has a negative effect on economic growth.